2022
DOI: 10.1186/s12933-022-01641-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of second-line antihyperglycemic drugs on the risk of chronic kidney disease: applying a target trial approach to a hospital-based cohort of Thai patients with type 2 diabetes

Abstract: Background The reno-protective effect of second-line treatments in type 2 diabetes has been assessed by clinical trials but generalizability to routine clinical practice is still uncertain. We aimed to assess the effectiveness of these treatments, when added to metformin, on the risk of chronic kidney disease (CKD). Methods A real-world, hospital-based, type 2 diabetes cohort was retrospectively assembled at Ramathibodi Hospital from 2010 to 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Moreover, SGLT2i can improve mitochondrial respiratory function and cardiac energy metabolism in the failing heart (31) when mitochondrial glucose oxidation and energy production is diminished. Extrapolating to the population level, we previously found that SGLT2i could directly lower CKD risk about 14% (32), and in this study, they could lower CVD risk of 2% relative to SUs with a number needed to treat of 140 and 20 per 1000 treated patients, i.e., for each 100 patients treated, we would prevent 14 CKD events and 2 CVD events over ~3.5 years of follow. Our current data also 3.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, SGLT2i can improve mitochondrial respiratory function and cardiac energy metabolism in the failing heart (31) when mitochondrial glucose oxidation and energy production is diminished. Extrapolating to the population level, we previously found that SGLT2i could directly lower CKD risk about 14% (32), and in this study, they could lower CVD risk of 2% relative to SUs with a number needed to treat of 140 and 20 per 1000 treated patients, i.e., for each 100 patients treated, we would prevent 14 CKD events and 2 CVD events over ~3.5 years of follow. Our current data also 3.…”
Section: Discussionmentioning
confidence: 59%